Analisa Emisi Gas Buang dan Bunyi Mesin Gokart 150 cc dengan Variasi Bahan Bakar dan RPM - Reza Anugrah Yulian; Agung Sudrajad; Imron Rosyadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2021)
Gokart were so popular on competition scene in Indonesia, using a two-stroke engine with an engine specification being regulated in race regulation. But for now, not only a two-stroke engine, many four-stroke engine gokart race held as it was safer for their driver and environment. It is necessary to do research on emissions and noise emmision so that they can be used as a reference in karting competitions and to maintain the safety of many people involved in the race. Emmision gas test conducted using gas analyzer, while for the noise emmision test using sound level meter. Data taken when the gokart engine in standby, neutral gear. Fuel kinds are the variants of this research, as different fuel means different octane number, such as Pertamax (92), Pertamax Plus (98) and Avgas (102), with data being taken at idle rpm, 3000, 5000, 7000 and 9000 for each different fuel. Data desired were CO, HC, O2, CO2, NOX gas concentration, while for the noise were the decibel value produced by engine. Best result achieved when using Pertamax Plus (98) for emmision gas, which is having emmision gas concentration of CO, HC, O2, CO2, NOX, with a value of 2.25%, 6012.4ppm, 1.98%, 14.33%, and 30.8ppm respectively. Worst result achieved when using Avgas (102), which is having emmision gas concentration of CO, HC, O2, CO2, NOX, with a value of 1.636%, 8849ppm, 0.42%, 17.63%, dan 19ppm respectively. While the noise emmision value based by engine rotation speed, which the speed affects the noise emmision as 1-5 db increasing for each 2000 Rpm increase. While looking for an octane number as a reference, the noise emmision value increase from 1 until 2 for each increase of the fuel octane number.Keywords: Emmision gas, noise emmision, two-stroke engine, gas analyzer, sound level meter.